In good company: association between fungal glycans generates molecular complexes with unique functions - Rodrigues, Marcio; Nimrichter, Leonardo (Frontiers in Microbiology, 2012)
The biological properties of fungal immunogens have historically utilized testing of isolated molecules. Recent findings, however, indicate that fungal glycans differing in structure and function can interact to form hybrid complexes with unique properties. In the pathogenic yeast Cryptococcus neoformans, chitin-like molecules associate with capsular glucuronoxylomannan (GXM) to form functionally distinct glycan complexes. Such interactions between glycans that result in the formation of structures with different functions strongly suggest that additional molecular complexes with unknown properties may exist in fungal pathogens. Moreover, the identification of these novel complexes has stimulated the search of new immunogens with potential to protect human and animal hosts against systemic mycoses.